1995
DOI: 10.1210/endo.136.5.7536659
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid regulation of insulin-like growth factor-binding protein-3.

Abstract: Short stature and decreased growth velocity are prominent features of endogenous and pharmacological glucocorticoid excess in children. Underlying processes may involve direct cellular effects or defective generation of insulin-like growth factors (IGFs) and/or IGF-binding proteins (IGFBPs), which modulate IGF-stimulated events and regulate growth. To evaluate potential mechanisms, we investigated the impact of dexamethasone (dex) on hepatic expression of IGFBP-3, the major carrier protein for IGFs. Using cocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
2
18
0
1
Order By: Relevance
“…In accordance with our results, dexamethasone and cortisol consistently decrease IGFBP-5 levels in bone cells (Okazaki et al 1994) and fibroblasts (Conover et al 1995). In contrast to our results, however, IGFBP-3 was found to be downregulated by dexamethasone in bone cells (Okazaki et al 1994), hepatic cells (Villafuerte et al 1995) and articular chondrocytes (DiBattista et al 1996). Regulation of IGFBP-3 by glucocorticoids was also studied in vivo.…”
Section: Figuresupporting
confidence: 90%
“…In accordance with our results, dexamethasone and cortisol consistently decrease IGFBP-5 levels in bone cells (Okazaki et al 1994) and fibroblasts (Conover et al 1995). In contrast to our results, however, IGFBP-3 was found to be downregulated by dexamethasone in bone cells (Okazaki et al 1994), hepatic cells (Villafuerte et al 1995) and articular chondrocytes (DiBattista et al 1996). Regulation of IGFBP-3 by glucocorticoids was also studied in vivo.…”
Section: Figuresupporting
confidence: 90%
“…Our previous studies demonstrated that the Kupffer and sinusoidal endothelial cells of the liver are the locus of both high basal expression of the IGFBP-3 gene and transcriptional regulation of IGFBP-3 by insulin (27,28). In this investigation, we used transient transfection of these nonparenchymal cells to identify sequences within the Ϫ1150 to Ϫ1124 bp region of the IGFBP promoter that are required for the response to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigations showed that IGFBP-3 mRNA is an abundant transcript in the liver and is secreted by the Kupffer and sinusoidal endothelial cells (27). Through sequential collagenase/Pronase treatment, we were able to isolate nonparenchymal cells that express IGFBP-3 and maintain the phagocytic function of Kupffer cells, and we have used this cultured cell model to study the mechanisms involved in the hormonal regulation of IGFBP-3.…”
mentioning
confidence: 99%
“…Several studies have indicated that these proteins are produced in different hepatic cell populations. Rat hepatocytes have been shown to secrete IGFBP-1, IGFBP-2, and IGFBP-4 (Bö ni-Schnetzler et al, 1990;Menuelle et al, 1995;Villafuerte et al, 1991), whereas IGFBP-3 expression was only found in Kupffer cells, endothelial cells, and hepatic stellate cells (Scharf et al, 1995(Scharf et al, , 1996(Scharf et al, , 1998aVillafuerte et al, 1994Villafuerte et al, , 1995. IGF-I is mainly released from hepatocytes (Kachra et al, 1991;Scharf et al, 1998a;Scott et al, 1985aScott et al, , 1985b.…”
mentioning
confidence: 99%